2021
DOI: 10.3390/nano11112953
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Macroscopic Fragmentation Characteristics under Hypervelocity Impact Based on MD and SPH Method

Abstract: This work investigates the difference in the fragmentation characteristics between the microscopic and macroscopic scales under hypervelocity impact, with the simulations of Molecular Dynamics (MD) and Smoothed Particle Hydrodynamics (SPH) method. Under low shock intensity, the model at microscopic scale exhibits good penetration resistance due to the constraint of strength and surface tension. The bullet is finally embedded into the target, rather than forming a typical debris cloud at macroscopic scale. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Several Atomistic simulation studies are done on hypervelocity impact such as to study the ballistic behavior of multilayer graphene polymer composite (MGPC) Molecular Dynamics (MD) simulations were done [16]. Fragmentation characteristic studies were done for macro and micro scales at high and low shocks using MD and Smoothed Particle Hydrodynamics (SPH) method [17]. The investigation of the effects of spacing of interlayers and the degree of oxidation of graphene oxide nanochannels was performed using MD simulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several Atomistic simulation studies are done on hypervelocity impact such as to study the ballistic behavior of multilayer graphene polymer composite (MGPC) Molecular Dynamics (MD) simulations were done [16]. Fragmentation characteristic studies were done for macro and micro scales at high and low shocks using MD and Smoothed Particle Hydrodynamics (SPH) method [17]. The investigation of the effects of spacing of interlayers and the degree of oxidation of graphene oxide nanochannels was performed using MD simulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Jiang et al [ 36 ] found that the presence of copper nanoparticle will trigger the formation of regular stacking fault in the single crystal aluminum under shock compression. Based on the smoothed particle hydrodynamics (SPH) method, Wu et al [ 37 ] discussed the differences in the fragmentation characteristics between the microscopic (atomic scale) and macroscopic scales under hypervelocity impact. In real applications, materials are usually exposed under a complex loading environment, e.g., electronics experience cyclic thermal and mechanical loadings during service [ 38 ].…”
mentioning
confidence: 99%